A new species of the genus Rhynchocalamus Günther, 1864 (Reptilia: Squamata: Colubridae) from Ilam province in western Iran - Fathinia, Behzad; Rastegar-Pouyani, Eskandar; Rastegar-Pouyani, Nasrullah; Darvishnia, Hamid (Zootaxa, 2017)
A new colubrid snake, Rhynchocalamus ilamensis sp. nov., is described from Ilam province, western Iran. The new species differs from other described congeners using both morphological and molecular analyses. Morphologically, the head and neck color patterns are the most obvious distinguishing traits of this species from its congeners. The new species is separated from other species of Rhynchocalamus by a genetic distance of 9–13% in the mitochondrial Cytb gene, with R. satunini and R. melanocephalus as the closest and farthest relatives, respectively. As well, a color-based revised key to the genus is provided.